2013
DOI: 10.1093/hmg/ddt184
|View full text |Cite
|
Sign up to set email alerts
|

A high-content, high-throughput siRNA screen identifies cyclin D2 as a potent regulator of muscle progenitor cell fusion and a target to enhance muscle regeneration

Abstract: Cell-mediated regenerative approaches using muscle progenitor cells hold promises for the treatment of many forms of muscle disorders. Their applicability in the clinic, however, is hindered by the low levels of regeneration obtained after transplantation and the large number of cells required to achieve an effect. To better understand the mechanisms that regulate the temporal switch of replicating muscle progenitor cells into terminally differentiated cells and to develop new strategies that could enhance mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…We also note that Cdc25 and Ccnd messenger RNAs that are targets of miR-195/497 likely also play a role in cell cycle withdrawal before terminal myogenic differentiation. The downregulation of Cdc25 in differentiating C2C12 myoblasts in the presence of miR-322/424 and miR-503 promotes cell cycle arrest necessary for terminal differentiation, while the downregulation of Ccnd2 in neonatal myoblasts enhances muscle cell fusion 32,33 . It remains to be seen whether miR-195/497 are also involved in cell cycle arrest during the terminal differentiation of myoblasts, and whether MuSCs require similar miRNA regulation of Cdc25/Ccnd mRNAs to form skeletal muscle fibres.…”
Section: Resultsmentioning
confidence: 99%
“…We also note that Cdc25 and Ccnd messenger RNAs that are targets of miR-195/497 likely also play a role in cell cycle withdrawal before terminal myogenic differentiation. The downregulation of Cdc25 in differentiating C2C12 myoblasts in the presence of miR-322/424 and miR-503 promotes cell cycle arrest necessary for terminal differentiation, while the downregulation of Ccnd2 in neonatal myoblasts enhances muscle cell fusion 32,33 . It remains to be seen whether miR-195/497 are also involved in cell cycle arrest during the terminal differentiation of myoblasts, and whether MuSCs require similar miRNA regulation of Cdc25/Ccnd mRNAs to form skeletal muscle fibres.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that CCND2 may also be downregulated in AML in association with the upregulation of miR133a and miR1 levels, similar to multiple myeloma. During development or regeneration of normal muscle, the downregulation of CCND2 strongly enhances the myogenic terminal differentiation of muscle progenitor cells [154] . Taken together, the upregulation of these myomiRs in par ticular cancers can contribute to the deregulated repression of cell factors such MST2, RHOA, CDC42, CCND2 and others, which then also contribute to dysregulation of other cell signalling pathways, potentiating oncogenesis and metastasis.…”
Section: Upregulated Myomirs In Cancermentioning
confidence: 99%
“…The possibility that the expression of dystrophin detected following engraftment of cells isolated from mdx 5cv mice transfected with PNA‐COR C may be the result of a small fraction of the muscle progenitor cells present in isolated muscles that had undergone repair rather than SCs is highly unlikely. First, extensive data in the literature have demonstrated that the number of cells required to achieve an effect are at least 1 order of magnitude higher than those used in this study . Second, it has been clearly demonstrated that the majority of differentiated muscle progenitor cells die shortly after transplantation .…”
Section: Discussionmentioning
confidence: 81%
“…For immunohistology, sections were incubated using a polyclonal antibody against dystrophin (Thermo Scientific Neomarkers, Fremont, CA, http://www.thermoscientific.com; 1:100) and detected with the Alexa 546‐coupled goat‐anti‐rabbit secondary antibody (Life Technologies; 1:500) . Hoechst staining (1:15,000) was used to visualize the nuclei within myofibers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation